Evaluation of peer‐mediated systems navigation for ageing families of individuals with developmental disabilities. Issue 5 (3rd March 2023) - Marsack‐Topolewski, C.; Milberger, S.; Janks, E.; Anderson, N.; Bray, M.; Samuel, P. S.
Abstract: Background: As individuals with intellectual and developmental disabilities (I/DD) age, services often diminish, with many family caregivers experiencing challenges finding and navigating services. The purpose of this study was to examine the benefits of a state‐wide family support project for ageing caregivers (50+) of adults with I/DD in accessing and using services. Method: A one‐group pre‐test–post‐test design was used to determine if participation in the MI‐OCEAN intervention grounded in the Family Quality of Life (FQOL) theory reduced ageing caregivers' ( n = 82) perceptions of barriers to accessing, using and needing formal services. Results: After participating in the study, there was a reduction in reported barriers to accessing services. There was also greater use and reduced need for 10 of the 23 listed formal services. Conclusions: Findings indicate that a peer‐mediated intervention grounded in FQOL theory can be beneficial in empowering ageing caregivers by reducing perceived barriers to accessing services and increasing their use of advocacy and support services.